(untitled) (Marketing Journal, 2026)
In this article, consumer brand loyalty and its economic impact on company revenue are analyzed. The process of brand loyalty formation and the main factors influencing it are described. In the course of the study, it is shown that revenue stability is ens ured through loyal customersʼ tendency toward repeat purchases. The importance of marketing strategies in increasing brand loyalty is revealed. It is substantiated that № 1 -SON YANVA R, 202 6-YIL 524 retaining existing customers is more effective than attracting new ones. Practical recommendations aimed at improving company performance are developed.